Cytotoxic Activity of Oleocanthal Isolated from Virgin Olive Oil on Human Melanoma Cells. (3rd July 2016) - Fogli, Stefano; Arena, Chiara; Carpi, Sara; Polini, Beatrice; Bertini, Simone; Digiacomo, Maria; Gado, Francesca; Saba, Alessandro; Saccomanni, Giuseppe; Breschi, Maria Cristina; Nieri, Paola; Manera, Clementina; et al.
ABSTRACT: Oleocanthal is one of the phenolic compounds of extra virgin olive oil with important anti-inflammatory properties. Although its potential anticancer activity has been reported, only limited evidence has been provided in cutaneous malignant melanoma. The present study is aimed at investigating the selective in vitro antiproliferative activity of oleocanthal against human malignant melanoma cells. Since oleocanthal is not commercially available, it was obtained as a pure standard by direct extraction and purification from extra virgin olive oil. Cell viability experiments carried out by WST-1 assay demonstrated that oleocanthal had a remarkable and selective activity for human melanoma cells versus normal dermal fibroblasts with IC50 s in the low micromolar range of concentrations. Such an effect was paralleled by a significant inhibition of ERK1/2 and AKT phosphorylation and downregulation of Bcl-2 expression. These findings may suggest that extra virgin olive oil phenolic extract enriched in oleocanthal deserves further investigation in skin cancer.